King O' the Cats - Shepard, Aaron (Atheneum Books for Young Readers, 2004)
A church sexton, known for his wild tales, has three weird encounters with magical cats and can't convince Father Allen that they really happened, until the priest's cat shows an intense interest. Have you ever seen a cat wearing a crown? Or noticed a group of cats hunting a dog? Young Peter Black has, but no one believes him! Peter is positive, though, that there's something a little odd about all the cats in town, and he's determined to get to the bottom of it. With vibrant illustrations by Kristin Sorra, Aaron Shepard retells a classic English folktale that will have readers looking twice at their cats! Meow, meow.